PROFESSIONALISM OF STATE CIVIL APPARATUS PERFORMANCE IN SERVING THE COMMUNITY AT THE DISTRICT LEVEL OF MALANG REGENCY - Suryo Hartoko; Lita Juniati (International Journal of Social Science, 2025)
Expertise or professionalism will be determined from the ability of a person to do work according to their duties. The results of work achievements are reviewed in terms of output according to plan and realization, routine in the same or different situations or conditions. This study aims to analyze the professionalism of employee performance (ASN) in serving the public in the District of Malang Regency. The type of study used is a qualitative study, analysis of study data using interactive analysis, namely; collecting data, reducing data, presenting data and drawing conclusions. The expertise or professionalism of employees in serving the public in the District of Malang Regency, from the aspect of knowledge based on a sufficient and adequate level of education. According to the data, that the ASN sub-district is capable and responsive to its duties, working until finished. The service runs quite effectively with professional support in work, according to the established procedures. The time limit for the service provided to the District is maximized, ASN's responsibility for work in service activities is optimal, where employees work according to procedures. For professional apparatus, they are able to avoid bad practices, violating ethics and morals. As able to respect, appreciate, obey and comply with the regulations, and be able to carry them out well. Increasing capacity competency towards professionalism must be developed, efforts to increase capacity are directed at the professionalism of the apparatus carried out systematically and continuously, so as to produce a professional apparatus with high quality performance.